Atlas Digital del Plan Regulador del Cantón de Alvarado, Cartago, Costa Rica. - Montenegro-Hernández, Esteban de Jesús (Instituto Tecnológico de Costa Rica, 2018)
In 2016, the regulatory plan of the canton of Alvarado was approved with a term of five years. In addition, in 2018 the Instituto Nacional de Vivienda y Urbanismo de Costa Rica (INVU), published a new manual of regulatory plans. For these reasons, in the municipality of Alvarado, the updating process was initiated and the need for management, organization, creation and updating of geographic information was identified. In this work, the objective of generating an information base for updating the regulatory plan of the canton of Alvarado was raised, on this basis the information was generated following recommendations for the organization, in consensus with another municipality in the region. Of the 110 geographical layers identified as necessary to update the regulatory plan of the canton of Alvarado, 24 were created, which corresponds to 21.81%. However, this work generated one of the most complex layers, which was the use of land, this is one of the most important for territorial ordering and was generated using the QGIS 3.0 program with the Semi-Automatic Classification Plugin. A classification with 85.252% of general accuracy was obtained, with 11 classes of land use. Other layers were generated such as road network, bridges, bus routes, watersheds, among others. In addition, officials of the municipality were trained on the structure of the generated base and the methodology for updating the information.
Trabajo de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2018.
Keywords: Sistema de Información Geográfica; Ordenamiento territorial; Plan regulador; Atlas digital; Research Subject Categories::NATURAL SCIENCES::Earth sciences::Exogenous earth sciences::Physical geography